2000
DOI: 10.1002/1097-4598(200012)23:12<1868::aid-mus11>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative electrophysiologic investigation for facial nerve outcome in acoustic neuroma surgery

Abstract: The prognostic significance of transcranial magnetic stimulation and nasal muscle F‐wave recording to predict postoperative facial nerve function was assessed in 24 patients with unilateral acoustic neuromas (mean diameter, 31 mm) and clinically intact facial nerve function. Latency of F waves and response to cortical magnetic stimulation, as well as F ratios, central motor conduction time, and the ratio of response latency to cortical and cisternal magnetic stimulation were significantly increased. Outcome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In addition to our previous work,17–20 this report confirms the feasibility of recording facial F waves from the nasalis muscle. The first detailed report on human facial F waves was published in 1973 16.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition to our previous work,17–20 this report confirms the feasibility of recording facial F waves from the nasalis muscle. The first detailed report on human facial F waves was published in 1973 16.…”
Section: Discussionsupporting
confidence: 83%
“…There is only one short communication concerning this topic 21. In the past 4 years, we have published several reports on the diagnostic value of nasalis muscle F waves in diseases of the intracranial portion of the facial nerve, especially in acoustic neuromas 17–20. We therefore thought it would be useful to compare the standard measurements (latencies, amplitudes, and ratios) obtained from a larger population of healthy subjects with those available from the literature and to establish reference values for the definition of abnormality both intraindividually and interindividually.…”
mentioning
confidence: 99%
“…Ideally, we would like to be able to predict the most likely outcome before performing the surgery. However, some studies have concluded that preoperative electrophysiological evaluation does not have prognostic value in terms of postoperative CNVII function [5, 12, 13]. This prompted us to evaluate the prognostic value of our preoperative electrophysiological testing results.…”
Section: Discussionmentioning
confidence: 99%